If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = x + -7is Reorder the terms: y = -7is + x Solving y = -7is + x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -7is + x
| 3(x+1)=x-21 | | 36-4b=4(-b+3) | | 36-4b=4b(-b+3) | | 40v+7=90v+30 | | 2(x+1)(x+5)-10=0 | | 100=x+(14+x) | | 3(x+1)=4-(x-3) | | (3y-5)+5y+20=135 | | 4k+18=3k-1 | | a^2-10k+30=0 | | 4(y-1)+3(y+2)=5(y-4) | | 4x-12=8x-16-4x | | 6m-m=.833(6m-10) | | 5x/2-4=2x-7/6 | | 14(t-2)+7t=(3t+3)-11 | | 2x^3-12x^2+23x-11=0 | | 5h-13=6h-16 | | 2q^2-3q=0 | | 12(3x+4)-5(2x+3)=6x-77 | | 4g-7=33 | | 6x^2-24x+23=0 | | 3p=15-2p | | 2q^2+3q=0 | | m^2-8mn+7n^2=0 | | 15-y+y=15 | | 4(1-p)=4p+4 | | 3x+1x=6 | | (8t+30)+(2t-16)=-22 | | x=15-y | | x+.67x=32.7 | | 10z-45=9z-45+z | | 2.5y+6=4.5y |